A sociology of women the intersection of patriarchy, capitalism, and colonization - Ollenburger, Jane C. (Prentice Hall, 1998)
Synthesizing the disciplines of sociology and women's studies, this book presents major theoretical frameworks on sex and gender stratification, taking a feminist sociological approach to the study of women in society to analyze women's positions within the institutions of work, education and the law. Integrates social class, race/ethnicity and gender as dimensions of equality across social issues. Explains basic sociological approaches, including functionalism, conflict theory and symbolic interactionism, and provides an overview of feminist theories. Analyzes trends in census data over the past two decades, and includes new sections on trends in women owned businesses and hate crimes. Discusses the global view of women in the labor force over the last three decades, and concludes with a section on Women and Aging that illustrates the compounded effects of the interconnections between class, race and gender issues on women as they progress through the course of life. For sociologists, social scientists, and those interested in women's studies